2008
DOI: 10.1177/0021943607309351
|View full text |Cite
|
Sign up to set email alerts
|

The Link Between Leadership Style, Communicator Competence, and Employee Satisfaction

Abstract: The current study examined the influence of supervisor communicator competence and leadership style on employee job and communication satisfaction. Participants were 220 individuals (116 men and 104 women) working full-time for a variety of companies in the Midwest. The findings indicated a strong relationship between supervisors' communicator competence and their task and relational leadership styles, with supervisor communicator competence being a stronger predictor of employee job and communication satisfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
185
5
13

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(218 citation statements)
references
References 36 publications
15
185
5
13
Order By: Relevance
“…This finding is in consonance with previous findings which has shown that QWL is positively linked with work performance (e.g. Azril, Jegak, Asiah, Azman, et al, 2010;Madlock, 2008). Perceived QWL was found to explain 75% of the variation in academic staff work performance.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…This finding is in consonance with previous findings which has shown that QWL is positively linked with work performance (e.g. Azril, Jegak, Asiah, Azman, et al, 2010;Madlock, 2008). Perceived QWL was found to explain 75% of the variation in academic staff work performance.…”
Section: Resultssupporting
confidence: 92%
“…Rossmiller (1992) found that QWL positively influenced the respect accorded to teachers, teacher participation in decisions affecting their work, professional collaboration and interaction, use of skills and knowledge and the teaching learning environment. Madlock (2008) argued that interpersonal …”
Section: Qwl and Work Performancementioning
confidence: 99%
“…Postoji niz studija iz različitih kulturoloških konteksta i okruženja koje istražuju konceptualni okvir koji uključuje stilove vodstva i zadovoljstvo poslom nastavnika / fakultetskog osoblja kako bi ispitale njihov međusobni odnos; ove studije otkrivaju da je taj odnos značajan (Al-Omari, 2008, Bogler, 2001, Dinham i Scott, 2000, Evans, 2001, Rad i Yarmohammadian, 2006. Studije o stilovima vodstva u odgojno-obrazovnim ustanovama pokazuju da u različitim kulturnim kontekstima različiti stilovi rukovođenja imaju značajan utjecaj na zadovoljstvo poslom nastavnika (Bogler, 2001, Madlock, 2008. Stoga istraživači preporučuju primjenu onih stilova vodstva za koje je utvrđeno da imaju značajan utjecaj na zadovoljstvo poslom nastavnika/fakultetskog osoblja u specifičnom kontekstu kako bi se poboljšala institucionalna učinkovitost (Dimmock i Walker, 2005, Nguni i sur., 2006.…”
Section: Utjecaj Stilova Vođenja šKolskog Ravnatelja Na šKolski Menadunclassified
“…In addition, the leadership practices employed by immediate managers lead to high level of job satisfaction (Kouzes et al 2007). Moreover, the leadership behavior has been found to contribute to job satisfaction ( Loke, 2001;Madlock, 2008;and Nguni, Sleegers, & Denessen 2006 ); job satisfaction and organizational commitment (AL-Hussami, 2008;Nguni et al 2006;Walumbwa, Orwa, Wang & lawler, 2005;westland, 2007). According to the above, researcher has hypothesized the following:…”
Section: Job Satisfaction As a Mediatormentioning
confidence: 99%